Lightening up a dark state of a Pentacene derivative via N-introduction - Ajdari, Mohsen; Stein, Arnulf; Hoffmann, Marvin; Müller, Matthias; Bunz, Uwe H. F.; Dreuw, Andreas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
N-Heteropolycyclic aromatic compounds are promising organic electron-transporting semiconductors for applications in field effect transistors. Here, we studied the structural and the electronic properties of an arrow-shaped N-heteropentacene derivative (triisopropylsilyl-dibenzodiazapentacene, TIPS-BAP) adsorbed on Au(111) in the monolayer and thin films using temperature-programmed desorption, vibrational and electronic high-resolution electron energy loss spectroscopy, and two-photon photoemission spectroscopy. In addition, we performed state-of-the-art quantum chemical calculations to further elucidate electronic properties. TIPS-BAP adopted an adsorption geometry in which the molecular backbone is oriented parallel to the Au(111) surface. We quantitatively determined the energetic position of several unoccupied as well as occupied molecular electronic states (transport states) with respect to the Fermi level of the gold substrate and resolved the optical gap (S0 → S1 transition) to be 1.9 eV. Compared to the corresponding polycyclic aromatic hydrocarbon TIPS-dibenzodipentacene (TIPS-BP), the optical gap is reduced by 0.2 eV due to nitrogen substitution. Based on our quantum chemical calculations, we attributed this effect to a stabilization of the first excited singlet state (S1) in the polar environment. Furthermore, an intense α-band (S0 → S2) in TIPS-BAP compared to TIPS-BP is observed due to an enhanced oscillator strength in the N-heteropolycyclic aromatic compound.